Analysis of the Impact of Investments in Disaster Risk Reduction and Prevention in Mexico : Case Study of Tabasco between 2007 and 2011 - Ishizawa, Oscar A.; Miranda, Juan Jose; Paredes, Miguel; de Haro, Itzel; Pedrozo, Adrian (World Bank, Washington, DC, 2017)
In the late nineties, the Mexican Government has implemented a fiscal risk management policy for natural disasters through the creation of the Mexican fund for natural disasters (FONDEN). The case of Tabasco presents a unique opportunity to analyze the impact of the investments in disaster risk reduction (DRR) in Mexico. The purpose of this report is to assess the impact of said investments in the state of Tabasco between 2007 and 2010 and to analyze, on the basis of empirical evidence, the effectiveness and efficiency of the implementation of risk reduction measures in the country. Due to its geographical location and hydrological characteristics, the state of Tabasco has been affected by 33 hydrological disasters, such as intense rainfall events, floods, and tropical storms, over the last ten years. The analysis confirms that the DRR measures implemented after the 2007 floods played a key role in reducing the damages and losses sustained in the 2010 events. The first section of this document presents background information on the state of Tabasco, how fiscal risk management is handled upon natural disasters in Mexico, and an overview on the creation and implementation of the Plan Hidrico Integral de Tabasco (PHIT). The second section presents the methodology used for assessing the impact of the investments in DRR measures implemented after 2007. The third section analyzes the advantages of both methods, the implications of the results obtained, and the potential of investments in DRR as a cost-effective measure to mitigate the impact of adverse weather events.